Quantification of femtomolar concentrations of the CYP3A substrate midazolam and its main metabolite 1′-hydroxymidazolam in human plasma using ultra performance liquid chromatography coupled to tandem mass spectrometry - Burhenne, Jürgen; Halama, Birte; Maurer, Monika; Riedel, Klaus-Dieter; Hohmann, Nicolas; Mikus, Gerd; Haefeli, Walter E. (Analytical and bioanalytical chemistry, 2012)
The benzodiazepine midazolam is a probe drug used to phenotype cytochrome P450 3A activity. In this situation, effective sedative concentrations are neither needed nor desired, and in fact the use of very low doses is advantageous. We therefore developed and validated an assay for the femtomolar quantification of midazolam and 1′-hydroxymidazolam in human plasma. Plasma (0.25 mL) and 96-well-based solid-phase extraction were used for sample preparation. Extraction recoveries ranged between 75 and 92% for both analytes. Extracts were chromatographed within 2 min on a Waters BEH C18 1.7 μm UPLC® column with a fast gradient consisting of formic acid, ammonia, and acetonitrile. Midazolam and 1′-hydroxymidazolam were quantified using deuterium- and 13C-labeled internal standards and positive electrospray tandem mass spectrometry in the multiple reaction monitoring mode, which yielded lower limits of quantification of 50 fg/mL (154 fmol/L) and 250 fg/mL (733 fmol/L) and a corresponding precision of <20%. The calibrated concentration ranges were linear for midazolam (0.05-250 pg/mL) and 1′-hydroxymidazolam (0.25-125 pg/mL), with correlation coefficients of >0.99. Within-batch and batch-to-batch precision in the calibrated ranges for both analytes were <14% and <12%. No ion suppression was detectable, and plasma matrix effects were minimized to <15% (<25%) for midazolam (1′-hydroxymidazolam). The assay was successfully applied to assess the kinetics of midazolam in two human volunteers after the administration of single oral microgram doses (1-100 μg). This ultrasensitive assay allowed us to quantify the kinetics of midazolam and 1′-hydroxymidazolam for at least 10 h, even after the administration of only 1 μg of midazolam. Open image in new window Figure UPLC/MS/MS quantification of femtomolar midazolam plasma concentrations